Konsepsi Hukum Progresif dalam Pengaturan Tindak Pidana Korupsi di Indonesia - Efraim Mbomba Reda; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2020)
Progressive law puts forward the sociology of law rather than legal certainty which is the focus of legal positivism. In Indonesia, this law was coined by Satjipto Rahardjo. This study aims to determine the formulation of progressive law in future criminal law, and to determine the actualization of the concept of progressive law in regulating corruption in Indonesia. The research method used is a normative legal research method with statute and conceptual approaches. The technique of collecting legal materials in this study is a descriptive method that aims to obtain the meaning of reality related to the problems to be discussed and solved in this study. The results show that in the current Criminal Code Bill, progressive law has been regulated, to be precise in Article 2 paragraph (1) and (2). Progressive law is also regulated in Law no. 48 of 2009 concerning Judicial Power. Then, the actualization of progressive law in regulating corruption in Indonesia is a judge with the powers that take into account the sociological context of society in making decisions. Judges, prosecutors and lawyers can certainly discuss together in eradicating corruption. Efforts are also being made to reconstruct and redefine the power of law enforcement. This arrangement can also encourage the KPK to be more progressive in eradicating corruption, as well as building law enforcers who have morality so that they can become role models and increase public participation, for example by forming NGOs in preventing or fighting corruption in various agencies.